Clinical Significance of Lymph Node Micrometastasis in pN0 Gastric Cancer Patients. (3rd March 2021) - Li, Yu; Wang, Dongsheng; Li, Yi; Liu, Xiaodong; Chen, Dong; Yuan, Chentong; Zhou, Yanbing
Abstract : Purpose . To investigate the relationship between lymph node micrometastasis (LNMM) and clinicopathological factors and to evaluate the prognostic effects of LNMM in pN0 gastric cancer (GC) patients. Methods . One hundred and seventy-two GC patients who received radical gastrectomy with D2 lymph node dissection were enrolled in the present study. 1371 negative lymph nodes from level 2 station confirmed by pathology were examined. The LNMM was diagnosed by telomeric repeat amplification protocol/enzyme-linked immunosorbent assay (TRAP-ELISA). The relationship between clinicopathological factors and LNMM was investigated by multivariate analysis. Survival analysis was performed to evaluate the effects of LNMM on prognosis. Results . LNMM was detected in 423 lymph nodes from 72 patients. The results showed that invasion depth (OR = 3.755, P = 0.004 ), TNM staging (OR = 3.152, P = 0.002 ), lymphatic invasion (OR = 2.178, P = 0.009 ), and tumor differentiation (OR = 1.266, P = 0.013 ) were independent risk factors associated with LNMM. Survival analysis showed that patients with LNMM had significantly worse 5-year survival compared with those without LNMM (42% vs. 76.4%, P < 0.05 ). Multivariate analysis demonstrated that LNMM, tumor size, Lauren type, invasion depth, and lymphatic invasion (P < 0.05 ) were independently factors associated with 5-year survival. Conclusions . The findings showed that tumor invasion depth, TNM staging, lymphatic invasion, and tumor differentiation were independent risk factors associated with LNMM occurrence. Moreover, LNMM is a clinically negative prognostic factor in pN0 GC patients.